2015
DOI: 10.1080/15592294.2015.1078050
|View full text |Cite
|
Sign up to set email alerts
|

Integrated methylome and transcriptome analysis reveals novel regulatory elements in pediatric acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer diagnosed in children under the age of 15. In addition to genetic aberrations, epigenetic modifications such as DNA methylation are altered in cancer and impact gene expression. To identify epigenetic alterations in ALL, genome-wide methylation profiles were generated using the methylated CpG island recovery assay followed by next-generation sequencing. More than 25,000 differentially methylated regions (DMR) were observed in ALL patients with »90% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 50 publications
3
71
0
Order By: Relevance
“…To determine if the trends observed in cell lines are consistent in primary cells, data generated from pre-B ALL patients and normal precursor B-cells was analyzed [23] . In these samples the gene expression of METTL3 was lower while FTO was higher in patients diagnosed with ALL compared to healthy donors ( Figure 2D), although the m 6 A status in these samples needs to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if the trends observed in cell lines are consistent in primary cells, data generated from pre-B ALL patients and normal precursor B-cells was analyzed [23] . In these samples the gene expression of METTL3 was lower while FTO was higher in patients diagnosed with ALL compared to healthy donors ( Figure 2D), although the m 6 A status in these samples needs to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…TRAF3 was found to be epigenetically regulated in three conditions: cardiac hypertrophy (25), acute lymphoblastic leukaemia (ALL) (26) and vascular recurrence in patients treated with clopidogrel (22).…”
Section: Traf3 Epigeneticsmentioning
confidence: 99%
“…Regarding the epigenetic regulation of TRAF3 in ALL, the genome-wide methylation profile was analysed in ALL using methylated CpG island recovery assay followed by next-generation sequencing (26). Then, the authors performed whole-transcriptome analysis and integrated this data with the methylation data.…”
Section: Traf3 Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant DNA methylation in vital regulatory regions of the genome, like enhancers, may cause initiation of many hematopoietic disease conditions including pre-B ALL. We have previously shown that aberrant methylation in enhancer regions was associated with the altered expression of neighboring genes involved in cell cycle processes, lymphocyte activation and apoptosis in pre-B ALL [10]. To further the understanding of the role that intergenic DNA methylation and/or differential eRNA expression plays in regulating the expression of target genes in pre-B ALL, the regulatory potential of putatively active enhancers has been investigated.…”
Section: Introductionmentioning
confidence: 99%